Relationship between Impaired Functional Stability, Back Pain and Fatigue - Ramunė Miliauskė; Lina Varnienė; Vilma Dudonienė (Lithuanian Sports University, 2020)
Musculoskeletal dysfunctions are commonly diagnosed in children and teenagers and have the tendency to grow [1]. Epidemiological research shows that non-specific low back pain occurs in childhood and the incidence increases from 13 to 51% [2]. According to research, every fifth school-age child is complaining of back pain [3]. The aim of the research was to define relationship between impaired functional stability, low back pain and fatigue in 9-12-yearold children. Height, weight as well as functional stability of 121 children raging in age from 9 to 12 years were assessed using Matthiass test [3]. Prevalence and intensity of low back pain as well as fatigue during the day and its intensity were assessed using pain and fatigue scales for children. Just one-fifth of the children were diagnosed with functional stability. Back pain was experienced by more than half of the children. Back pain in girls was significantly higher than that in boys. Singificantly more girls felt fatigue during the day compared to boys. Back pain can be influenced by the emergence of poor functional stability - significantly more children who failed in functional stability test reported back pain. Also back pain in children can be related to tiredness during the day. Keywords: functional stability, back pain, children, fatigue.